Vascular endothelial overexpression of human CYP2J2 (Tie2-CYP2J2 Tr) modulates cardiac oxylipin profiles and enhances coronary reactive hyperemia in mice. - Ahmad Hanif; Matthew L Edin; Darryl C Zeldin; Christophe Morisseau; John R Falck; Mohammed A Nayeem (PLoS ONE)
Arachidonic acid is metabolized to epoxyeicosatrienoic acids (EETs) by cytochrome (CYP) P450 epoxygenases, and to ω-terminal hydroxyeicosatetraenoic acids (HETEs) by ω-hydroxylases. EETs and HETEs often have opposite biologic effects; EETs are vasodilatory and protect against ischemia/reperfusion injury, while ω-terminal HETEs are vasoconstrictive and cause vascular dysfunction. Other oxylipins, such as epoxyoctadecaenoic acids (EpOMEs), hydroxyoctadecadienoic acids (HODEs), and prostanoids also have varied vascular effects. Post-ischemic vasodilation in the heart, known as coronary reactive hyperemia (CRH), protects against potential damage to the heart muscle caused by ischemia. The relationship among CRH response to ischemia, in mice with altered levels of CYP2J epoxygenases has not yet been investigated. Therefore, we evaluated the effect of endothelial overexpression of the human cytochrome P450 epoxygenase CYP2J2 in mice (Tie2-CYP2J2 Tr) on oxylipin profiles and CRH. Additionally, we evaluated the effect of pharmacologic inhibition of CYP-epoxygenases and inhibition of ω-hydroxylases on CRH. We hypothesized that CRH would be enhanced in isolated mouse hearts with vascular endothelial overexpression of human CYP2J2 through modulation of oxylipin profiles. Similarly, we expected that inhibition of CYP-epoxygenases would reduce CRH, whereas inhibition of ω-hydroxylases would enhance CRH. Compared to WT mice, Tie2-CYP2J2 Tr mice had enhanced CRH, including repayment volume, repayment duration, and repayment/debt ratio (P < 0.05). Similarly, inhibition of ω-hydroxylases increased repayment volume and repayment duration, in Tie2-CYP2J2 Tr compared to WT mice (P < 0.05). Endothelial overexpression of CYP2J2 significantly changed oxylipin profiles, including increased EETs (P < 0.05), increased EpOMEs (P < 0.05), and decreased 8-iso-PGF2α (P < 0.05). Inhibition of CYP epoxygenases with MS-PPOH attenuated CRH (P < 0.05). Ischemia caused a decrease in mid-chain HETEs (5-, 11-, 12-, 15-HETEs P < 0.05) and HODEs (P < 0.05). These data demonstrate that vascular endothelial overexpression of CYP2J2, through changing the oxylipin profiles, enhances CRH. Inhibition of CYP epoxygenases decreases CRH, whereas inhibition of ω-hydroxylases enhances CRH.